2022
DOI: 10.1002/aenm.202202703
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Ordered Atomic Donor–Acceptor Architectures in bcc IrGa Intermetallic Compounds toward Highly Electroactive and Stable Overall Water Splitting

Abstract: Benefiting from ordered atomic structures and strong d‐orbital interactions, intermetallic compounds (IMCs) are promising electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Herein, the body‐centered cubic IrGa IMCs with atomic donor–acceptor architectures are synthesized and anchored on the nitrogen‐doped reduced graphene oxide (i.e., IrGa/N‐rGO). Structural characterizations and theoretical calculations reveal that the electron‐rich Ir sites are atomically dispersed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The enhanced HER kinetics was ascribed to the charge redistribution on the ordered Ir 3 V surface with a maximized number of neighboring Ir/V sites compared to the disordered counterpart, thereby promoting water dissociation on the electron‐deficient V sites. bcc intermetallic IrGa nanoparticles on N‐doped rGO exhibited excellent performance toward both HER and OER, thus having a low cell voltage of 1.51 V to achieve 10 mA/cm 2 for the overall water splitting in alkaline condition 61 . DFT calculations suggested that the high performance could be ascribed to the creation of electron‐rich Ir via incorporating Ga with lower electronegativity, such that the electron transfer between Ir and the adsorbed species could be promoted, thereby decreasing the energy barriers of the potential determining steps.…”
Section: Electrocatalytic Applications Of Intermetallic Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced HER kinetics was ascribed to the charge redistribution on the ordered Ir 3 V surface with a maximized number of neighboring Ir/V sites compared to the disordered counterpart, thereby promoting water dissociation on the electron‐deficient V sites. bcc intermetallic IrGa nanoparticles on N‐doped rGO exhibited excellent performance toward both HER and OER, thus having a low cell voltage of 1.51 V to achieve 10 mA/cm 2 for the overall water splitting in alkaline condition 61 . DFT calculations suggested that the high performance could be ascribed to the creation of electron‐rich Ir via incorporating Ga with lower electronegativity, such that the electron transfer between Ir and the adsorbed species could be promoted, thereby decreasing the energy barriers of the potential determining steps.…”
Section: Electrocatalytic Applications Of Intermetallic Nanocrystalsmentioning
confidence: 99%
“…High-surface-area substrates can enlarge the interparticle distance and provide a support for the migration and diffusion of metal atoms, such that particle aggregation can be mitigated to some extent during annealing. Various two-dimensional (2D) substrates have been used for this purpose, such as carbon black, 54,59 GO, 56,60,61 and metal oxides. 62 The annealing temperature and period are determinant parameters for manipulating the degree of ordering of intermetallic nanocrystals.…”
Section: Conventional Approach-thermal Annealingmentioning
confidence: 99%
“…[20][21][22][23][24] Theoretically, constructing an intermetallic with an ordered atomic arrangement can enhance the electrocatalytic activity and durability, and reduce the use of noble metals. 25,26 Alloys modify the electronic state of catalytically active elements through electronic effects, and the degree of modication depends largely on the nature and composition of the second metal. 27 RE elements have a unique electronic structure of [Xe]4f n-1 5d 0-1 6s 2 (n = 1-15), which can provide an additional route for adjusting the electronic structure of catalytically active elements.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] To enhance the HER performance and decrease the consumption of Ru, the fabrication of composition-dened and atomic ordered Ru-based intermetallic compounds (IMCs) is a promising strategy. [22][23][24][25][26] The insertion of a relatively lower electronegative metal (i.e., Ga) could create electron-rich environments for the Ru atoms, [27][28][29][30] which can modulate the electronic structure of Ru sites and improve the HER performance. In addition, the higher mixing enthalpy and stronger interactions between Ru and Ga atoms can rmly stabilize Ru atoms during the electrochemical measurements in both acidic and alkaline electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…22–26 The insertion of a relatively lower electronegative metal ( i.e. , Ga) could create electron-rich environments for the Ru atoms, 27–30 which can modulate the electronic structure of Ru sites and improve the HER performance. In addition, the higher mixing enthalpy and stronger interactions between Ru and Ga atoms can firmly stabilize Ru atoms during the electrochemical measurements in both acidic and alkaline electrolytes.…”
Section: Introductionmentioning
confidence: 99%